Financing Climate Change Adaptation in Transboundary Basins : Preparing Bankable Projects - World Bank (World Bank, Washington, DC, 2019)
Water, climate and finance know no borders. This brings challenges and opportunities: The majority of freshwater worldwide flows in transboundary basins and most climate change impacts are felt through the water cycle. Transboundary cooperation in climate change adaptation is crucial for preventing mal-adaptation and making adaptation in shared basins more effective. However, many basins struggle in accessing funds for climate change adaptation. River basin organizations can play a valuable role in this fund-raising process. Understanding the special risks and complexities of transboundary river basin projects is critical to preparing bankable project proposals that will attract public and private financing partners. This report highlights the challenges and opportunities countries face in accessing financial resources for climate adaptation in transboundary river basins. Outlining basic characteristics and criteria for the preparation of bankable project proposals, the report is a guide for those working on climate change adaptation in transboundary river basins.